2016
DOI: 10.1039/c5ob02250a
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid of thiazolidinone with the hydroxamate scaffold for developing novel histone deacetylase inhibitors with antitumor activities

Abstract: A series of novel histone deacetylase (HDAC) inhibitors were designed, synthesized and evaluated based on the strategies of a hybrid of the classic pharmacophore of HDAC inhibitors with the thiazolidinone scaffold. Some of the compounds 12i showed potent HDAC1 inhibition with nM IC50 values, more importantly, compound displayed much better anti-metastatic effects than vorinostat (SAHA) against migration of the A549 cell line. Further mechanism exploration implied that compound 12i may inhibit tumor metastasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…The PASS analysis results indicated that the predicted highest probability of biological activity (Pa) was for histone deacetylase (HDAC) SIRT1 enzyme (Table S2 ). The PASS prediction results are supported by the reported HDAC inhibitory activity of various adamantane 52 54 and thiazole 28 , 29 , 55 59 derivatives.…”
Section: Resultssupporting
confidence: 62%
“…The PASS analysis results indicated that the predicted highest probability of biological activity (Pa) was for histone deacetylase (HDAC) SIRT1 enzyme (Table S2 ). The PASS prediction results are supported by the reported HDAC inhibitory activity of various adamantane 52 54 and thiazole 28 , 29 , 55 59 derivatives.…”
Section: Resultssupporting
confidence: 62%
“…Valproic acid (VPA) and sodium phenylbutyrate are two representative compounds of this class, and they are still under investigation for their anticancer efficacies in clinical trials 125 . Our laboratory has discovered a new series of novel hydroxamate‐based HDAC inhibitors with significant antitumor effects and these compounds significantly suppresses the growth and metastasis of some solid tumors in mouse models 126–129 . Further research found that this type of HDACIs has a potent sensitizing effect on non‐small cell lung cancer (NSCLC) that is counteractive to the EGFR TKI drug erlotinib, and thus restored the therapeutic effect of erlotinib in NSCLC 130 .…”
Section: Drug Discovery Strategies Targeting the Key Proteins Involve...mentioning
confidence: 99%
“…125 Our laboratory has discovered a new series of novel hydroxamate-based HDAC inhibitors with significant antitumor effects and these compounds significantly suppresses the growth and metastasis of some solid tumors in mouse models. [126][127][128][129] Further research found that this type of HDACIs has a potent sensitizing effect on non-small cell lung cancer (NSCLC) that is counteractive to the EGFR TKI drug erlotinib, and thus restored the therapeutic effect of erlotinib in NSCLC. 130 Moreover, the subsequently optimized lead compound showed great potential in preclinical studies of BC.…”
Section: Targeting the Epigenetic Regulationmentioning
confidence: 99%
“…HDACs were involved in condensing chromatin so can downregulating many genes expression, while HATs can removes the positive charge on the histones, so the chromatin can transform to a more open structures and active the transcription. In recently study global hypoacetylation of histone is also correlated with numerous specific processes like the occurrence and development of tumor, with the features of uncontrolled cell growth, proliferation and so on 1,2 . Now, 11 classical human HDACs have been identified and grouped into three Classes based on their sequence homology to yeast orthologues Rpd3, Hdal and Sir2, respectively 3 .…”
Section: Introductionmentioning
confidence: 99%